Workshop Pengenalan Web dan CSS Dasar Pada Mahasiswa Universitas Muhammadiyah Jambi - Shandy Amandha; Rian Dani; Trie Hierdawati; Armandito; Bima Rahmat (Pusat Riset dan Inovasi Nasional, 2024)
This workshop is specifically aimed at beginners in web development who want to learn more about HTML and CSS. Participants (students) will be guided through basic HTML material, including content structure, and an introduction to CSS, covering layout principles and responsive design implementation skills. Students will be able to create visually appealing web pages, responsive to various screen sizes. They not only understand the basic theory of HTML and CSS, but can also produce web pages that adapt smoothly on a variety of devices, meeting the demands of modern web design. Through workshops or community service activities, it is targeted to provide benefits to students at Muhammadiyah University, Jambi. Providing learning insights and knowledge in using and utilizing the Internet by providing materials and discussions. Training workshop activities contain knowledge or learning material, providing applications and examples, and questions and answers.